(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Even though Reverse Osmosis (RO) is one of the greatest prominent and effective techniques for the waste water treatment, but it also generates large amount of concentrated brine known as RO reject. The present work aimed to achieve maximum efficiency as well as optimal conditions for the treatments of petro-chemical RO reject by electro-oxidation process using graphite electrodes. The Response of the Surface Methodology under Central Composites Design was utilized to examine the effects of various independent parameters likes reaction time, pH, current density as well as electrode distance on the removal efficiency. The maximum total dissolved solid (TDS) removal was obtained 51.16% at optimum situation. 1st as well as 2nd orders kinetic model were fitted to described the finest kinetic model for TDS removal. The effectiveness of electro-oxidation therapy in removing TDS was studied. During EO treatment, TDS removal was found to be substantially influenced by solution reaction time, pH, current density, and electrode gap.